In vivo assessment of basic 2-nitroimidazole radiosensitizers. - Williams, M. V. (Nature Publishing Group, 1982)
The radiosensitizing efficiencies of 4 structural analogues of misonidazole (MISO) have been compared with that of the parent compound. Three of these were charged basic compounds, previously shown in vitro to be 10 times more efficient. Enhancement ratios were measured from pairs of tumour growth-delay curves for the mouse fibrosarcoma SA Fab. Two routes of administration and ranges of drug dose and intervals between injection and irradiation were tested. Drug concentrations in blood, brain and tumor were measured using high-performance liquid chromatography. The peak concentration in tumours coincided with the peak in radiosensitization: 20 min after i.v. injection and 40 min after i.p. injection. The concentration in tumours was similar for either route. Comparison of radiosensitizing efficiency on the basic of equal administered dose showed no difference between the 5 compounds, but after equimolar doses the charged compounds achieved lower tumour concentrations. Comparison of sensitizing efficiency on the basis of tumour concentration showed that they were 3 times more potent than MISO, as predicted from their higher electron-affinity. The resultant improvement in radiosensitization at low, clinically relevant, concentrations is so slight that any therapeutic benefit would depend on reduced drug toxicity in man.